Pharmacological HIF1 Inhibition Eliminates Downregulation of the Pentose Phosphate Pathway and Prevents Neuronal Apoptosis in Rat Hippocampus Caused by Severe Hypoxia - Vetrovoy, Oleg; Sarieva, Kseniia; Lomert, Ekaterina; Nimiritsky, Peter; Eschenko, Natalia; Galkina, Olga; Lyanguzov, Andrey; Tyulkova, Ekaterina; Rybnikova, Elena (Journal of molecular neuroscience, 2020)
The pentose phosphate pathway (PPP) of glucose metabolism in the brain serves as a primary source of NADPH which in turn plays a crucial role in multiple cellular processes, including maintenance of redox homeostasis and antioxidant defense. In our model of protective mild hypobaric hypoxia in rats (3MHH), an inverse correlation between hypoxia-inducible factor-1 (HIF1) activity and mRNA levels of glucose-6-phosphate dehydrogenase (G6PD), the key enzyme of PPP, was observed. In the present study, it was demonstrated that severe hypobaric hypoxia (SH) induced short-term upregulation of HIF1 alpha-subunit (HIF1α) in the hippocampal CA1 subfield and decreased the activity of G6PD. The levels of NADPH were also reduced, promoting oxidative stress, triggering apoptosis, and neuronal loss. Injection of a HIF1 inhibitor (HIF1i), topotecan hydrochloride (5 mg/kg, i.p.), before SH prevented the upregulation of HIF1α and normalized G6PD activity. In addition, HIF1i injection caused an increase in NADPH levels, normalization of total glutathione levels and of the cellular redox status as well as suppression of free-radical and apoptotic processes. These results demonstrate a new molecular mechanism of post-hypoxic cerebral pathology development which involves HIF1-dependent PPP depletion and support a recently suggested injurious role of HIF1 activation in the acute phase of cerebral hypoxia/ischemia. Application of PPP stimulators in early post-hypoxic/ischemic period might represent a promising neuroprotective strategy. Graphical abstract HIF1-dependent down-regulation of the pentose phosphate pathway contributes to the hypoxia-induced oxidative stress and neuronal apoptosis in the rat hippocampus